Implementasi Kepemimpinan Kepala Sekolah Pada Profesi Kependidikan - Arimbi Syahkila Simangunsong; Zuchairunnisa Zuchairunnisa; Aina ul- mardiyah Ray; Irma Tussa’diyah Hasibuan; Yusuf Ali Ahmad; Soleh Parlindungan Tambak (Peneliti.net, 2022)
The benefits expected in this research are expected to add insight and Knowledge about Implementation Of Principal Leadership In The Education Profession At the UINSU Laboratory Madrasah Aliyah School. This study uses a qualitative design through a case study approach. Type The case studies used use facts and phenomena found by researchers and obtain data from the field in connection with Leadership in Learning. The research location is at the UINSU Laboratory Madrasah Aliyah School. Results of This research is: Principal leadership at Madrasah Aliyah UINSU Laboratory aims to encourage every member of the teacher and students to be enthusiastic in achieving goals and also aims to motivate and improve different performances according to the type or style of leadership applied by the Madrasah principal Aliyah UINSU Laboratory.